Multi-alternative model of situational analysis of the air environment - Корчунов, Д. О.; Харченко, В. П. (Proceedings of National Aviation University (archive), 2002)
The main advantages of the multi-alternative model of situational analysis of the district- the situation over the collision risk assessment model used, an example of influence mean square error on azimuth on the probability of occurrence of the situation